Innovatie vernieuwd Opening in viervoud - Wetenschappelijke Raad voor het Regeringsbele (WRR Rapporten, 2008)
Innovation means more than having the right ideas and knowledge. It is also a matter of organization and skills. Dutch society is in need of a new, open innovation policy with special attention for social innovation. In this report the WRR does recommendations to improve the innovation policy in the Netherlands. The new policy it suggests gives space to surprises, to challenges and crosses borders. It stimulates cooperation between companies and institutions. It shows new ways of organizing that stimulates and gives room to the real innovators.